TOL is a broad-host-range plasmid. - Benson, S (1978)
We readily isolated insertions of the carbenicillin resistance element Tn401 into the TOL plasmid in Pseudomonas putida. Hybrid TOL::Tn401 plasmids stably express the Cbr phenotype in Pseudomonas aeruginosa and Escherichia coli. Whereas the replicative and conjugative functions are expressed in both hosts, the ability to grow on m-toluate is only expressed in the Pseudomonas species.